2017
DOI: 10.1002/2017wr020834
|View full text |Cite
|
Sign up to set email alerts
|

Using system dynamics simulation for assessment of hydropower system safety

Abstract: Hydropower infrastructure systems are complex, high consequence structures which must be operated safely to avoid catastrophic impacts to human life, the environment, and the economy. Dam safety practitioners must have an in‐depth understanding of how these systems function under various operating conditions in order to ensure the appropriate measures are taken to reduce system vulnerability. Simulation of system operating conditions allows modelers to investigate system performance from the beginning of an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…A more detailed description of the components, their operating states, and impacts is provided in Supplementary materials File S1. A simulation model of a hydropower system, described in detail in by King et al [9], was adapted for this case study with simplified components shown in Figure 14. The component interactions are represented through feedback loops that determine the system behavior.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A more detailed description of the components, their operating states, and impacts is provided in Supplementary materials File S1. A simulation model of a hydropower system, described in detail in by King et al [9], was adapted for this case study with simplified components shown in Figure 14. The component interactions are represented through feedback loops that determine the system behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Simulation model development using system dynamics simulation, as proposed by King et al [9], is described in the following section, which details how to develop the model to facilitate inputting of events (such as failures) and their parameters (such as the outage lengths). Next, a description of the Monte Carlo generation of simulation parameters is provided, followed by a description of the simulation process framework and event influence considerations in scenario analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the SD approach, Xu et al [38] constructed a water resources SD model to analyze the water resource sustainability of the Yellow River in China. King et al [48] used SD simulations to assess hydropower system safety. Yuan et al [35] developed a self-optimization system dynamics simulation model of real-time short term cascade hydropower system and extracted operation rules for short-term hydropower reservoir operation by SD simulation.…”
Section: Introductionmentioning
confidence: 99%